Domestic and International Macroeconomic Variables on Indonesian Sharia Stock Index with Vector Error Correction Model Approach - Nofrianto; Faqih Muhammad Arif (AL-MUZARA'AH, 2023)
The fluctuating movement of the Indonesian Sharia Stock Index (ISSI) is thought to be caused by domestic and international macroeconomic factors. Previous research revealed inconsistent results regarding the factors that influence ISSI price movements with the research time horizon generally in the short to medium term. This study aims to analyze and see the magnitude of the influence of domestic and international macroeconomic variables on ISSI. This study uses the Vector Error Correction Model (VECM) method with monthly time series data from May 2011 to July 2022. The results of the study show that in the long-term, inflation, amount of money supply, world oil price, and Dow Jones Islamic Market US have a significant effect on ISSI. In the short term, only world gold price has a significant effect on ISSI. BI repo rate and exchange rate did not significantly affect ISSI in the short and long term. The Indonesian Sharia Stock Index reaches stability the fastest when it responds to shocks in gold prices. This study recommends the promotion of ISSI and Islamic finance, careful consideration in investment decisions by companies and investors, and the need for an early warning system in the Islamic capital market to anticipate the financial crisis.